2002
DOI: 10.1152/jappl.2002.92.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eccentric contraction-induced injury on force and intracellular pH in rat skeletal muscles

Abstract: The effect of eccentric contraction on force generation and intracellular pH (pH(i)) regulation was investigated in rat soleus muscle. Eccentric muscle damage was induced by stretching muscle bundles by 30% of the optimal length for a series of 10 tetani. After eccentric contractions, there was reduction in force at all stimulation frequencies and a greater reduction in relative force at low-stimulus frequencies. There was also a shift of optimal length to longer lengths. pH(i) was measured with a pH-sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 35 publications
4
28
0
Order By: Relevance
“…This difference likely indicates that alteration o f pH homeostasis could be associ ated to the contraction modality used in EIMD (i.e., volun tary vs. electrically evoked). Our findings are reinforced by the significant decrease in intracellular pH resulting from elec trically evoked eccentric contractions in mouse muscle (50). From a physiological point of view, pH homeostasis in skele tal muscle relies on the balance between proton accumulation and removal mediated by transporters located at the sarcolemma (22).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This difference likely indicates that alteration o f pH homeostasis could be associ ated to the contraction modality used in EIMD (i.e., volun tary vs. electrically evoked). Our findings are reinforced by the significant decrease in intracellular pH resulting from elec trically evoked eccentric contractions in mouse muscle (50). From a physiological point of view, pH homeostasis in skele tal muscle relies on the balance between proton accumulation and removal mediated by transporters located at the sarcolemma (22).…”
Section: Discussionsupporting
confidence: 64%
“…More over, the specific motor unit recruitment imposed by iso metric NMES contractions [for review, see (36)] has been shown to induce a decrease in M-wave amplitude indicating diminished sarcolemma excitability (51) compared to volun tary eccentric EIMD (6). Thus, electrically evoked contrac tions, inducing larger muscle fiber disruption and a higher inflammatory response compared to voluntary ones (8), could also generate larger alteration of sarcolemma (3) leading to dysregulation of pH through the impaired activity of the Na+/H+exchangers and then an abnormal intracellular pH regulation (50). However, it is well documented that pH must be maintained at a value at which all pH-dependent proton fluxes add up to the very low rate necessary in resting muscle (28).…”
Section: Discussionmentioning
confidence: 99%
“…Our previously published data (Kyparos et al 2001) showed decrements in unfused (40 Hz) and fused (80 Hz) tetanic force production, as well as a higher fatigue rate at a very low stimulation frequency (4 Hz for 5 min) in male rats following the same downhill running exercise protocol. Yeung et al (2002) found a reduction in submaximal unfused tetanic force at 40 and 70 Hz, as well as in maximal tetanic force at 100 Hz after a series of 10 tetanic eccentric contractions induced by stretching rat soleus muscle bundles by 30% of their optimal length, yet the relative force reduction was greater at 10 and 20 Hz. The force deficit was attributed to the failure of the damaged sarcomeres to produce tension and (or) the disruption of the membrane systems involved in E-C coupling.…”
Section: Ovx-ed0mentioning
confidence: 84%
“…The delayed force recovery, especially in LF torque, indicates a possible contribution of exercise-induced muscle damage to the observed contractile force loss (Edwards et al 1977;Yeung et al 2002). Further evidence for exercise-induced muscle damage was found from the elevated serum CK activity post exercise, which has been used as an indirect marker of muscle damage in several studies (for a review see Warren et al 1999).…”
Section: Discussionmentioning
confidence: 99%